Les ouvriers des munitions des Alliés ripostent à Hitler par les fabriques britanniques!
Colour images in grid; on the top, military action; on the bottom, ammunition factories scenes Suggested translation: The ammunition workers of the Allies fight Hitler from the British factories! PO-1269